The Reality of Marketing the Islamic University's Educational Services in the Gaza Strip and its Impact on the Decision to Enter Them from the Point of View of the University's First- Level Students - Bashir, Maisoon Khalil (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to assess the reality of marketing educational services at the Islamic University in the Gaza Strip and its impact on the decision to join it from the viewpoint of first- level students at the university. The study adopted the descriptive and analytical approach, and the tool was a questionnaire. It was distributed to a simple stratified random sample of (355) male and female students from all colleges of the first level (BA), and the SPSS program was used in the data analysis. The results of the study showed that the marketing of educational services from the viewpoint of the first- level students obtained an overall average (3.75 out of 5), with a grade of (large), and the field of promotion came first with an arithmetic average ((3.86), followed by the field of public relations with an average ((3.83) and the third in the field of advertising with an average (3.75) and fourth in the field of factors helping to attract students with an average of (3.72) and finally the field of direct marketing with an average of (3.57), and it was found that the size of the effect amounted to (0.85). It indicates (large) correlation coefficients and the existence of a positive relationship of (α≤0.05) Between the marketing of educational services at the Islamic University in the Gaza Strip in its five dimensions and the decision to enroll students in the university reached (0.83), indicating (large) correlation coefficients. Based on the results of the study, the researcher presented a number of recommendations and proposals, including: The university forming marketing teams that keep pace with the technical and technological developments in the world Marketing because of the great importance attached to the university in all respects, especially attracting students and attracting them to the university's specializations.
Keywords: reality; marketing educational services; impact; the decision to enroll students; the Islamic University; Gaza strip